Predictive Value of Plasma MicroRNA-216a/b in the Diagnosis of Esophageal Squamous Cell Carcinoma. (18th February 2016) - Dong, Shuling; Yin, Huiqing; Dong, Cuicui; Sun, Kaiyan; Lv, Pin; Meng, Weiwei; Ming, Liang; He, Fucheng
Abstract : Esophageal squamous cell carcinoma (ESCC) is a common human malignancy with poor survival, which was usually diagnosed at an advanced stage. MicroRNAs (miRNAs), a class of single stranded noncoding RNAs with only 17–25 ribonucleotides, were demonstrated to play an important role in lots of cancers. In the recent years, increasing evidence revealed that circulating miRNAs exhibited great potential in the diagnosis of various types of cancers. The present study was designed to evaluate the diagnostic value of plasma miRNA-216a/b for ESCC. Our results showed that the expression level of plasma miRNA-216a/b was significantly lower in ESCC patients compared with that of healthy controls. The receiver operating characteristic (ROC) curve analysis yielded an area under the ROC curve (AUC) value of 0.877 [95% CI (confidence interval): 0.818–0.922] for miRNA-216a and 0.756 (95% CI: 0.685–0.819) for miRNA-216b. Clinical data indicated that plasma miRNA-216a/b were inversely correlated with lymph node metastasis and TNM stage. Additionally, the plasma miRNA-216b expression level was significantly upregulated in postoperative samples compared to preoperative samples. Our study, for the first time, demonstrated that plasma miRNA-216a/b might serve as potential biomarkers for the diagnosis of ESCC and dysregulation of miRNA-216a/b might be involved in the progression of ESCC.